Safeguarding Indigenous Rights and Territories: Integrating Dayak Ngaju Wisdom in Peatland Ecosystem Management - Sumarni Sumarni; Muhammad Ery Wijaya; Astrid Meilasari Sugiana (Faculty of law Udayana University, 2023)
In Indonesia, the legal system heavily favors state ownership of land, leading to the marginalization of Indigenous peoples and their traditional land management practices. The prioritization of economic development over environmental and cultural conservation has resulted in a limited understanding of the value of the peatland ecosystem for Indigenous Dayak communities, leading to inappropriate and ineffective peatland management policies. To address these challenges, this research adopts a descriptive qualitative approach, utilizing a cross-sectional research design that includes in-depth interviews and literature study to gather and analyze data from Indigenous Dayak Ngaju communities in Tumbang Nusa and Pilang villages, Pulang Pisau regency, Central Kalimantan province. The study uncovers that the Indigenous Dayak Ngaju community has established a zonation system for peatland use, comprising separate areas for settlement, farming, and forest protection (Pukung Pahewan). The creation of specific policies for managing sacred areas is crucial to preserving Indigenous values and practices. Moreover, the absence of free, prior, and informed consent in certain policies and programs, such as the Mega Rice project, Food Estate program, and Zero-burning policy, has caused social conflicts within the Indigenous Dayak community, leading to the destruction of their livelihoods. Despite existing laws in Indonesia that acknowledge the rights of Indigenous peoples and safeguard their customary lands, the implementation and enforcement of these laws have proven weak and inconsistent.